2020
DOI: 10.1186/s40942-020-00211-6
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic complications associated with suprachoroidal buckling

Abstract: Background: Multiple surgical techniques exist for the repair of rhegmatogenous retinal detachments (RRD). Suprachoroidal buckling (SCB), consisting of injecting viscoelastic material in the suprachoroidal space to allow chorioretinal apposition, has been recently described in the repair of RRD. The aim of this study is to report the complications of SCB and to propose measures to decrease their incidence during the learning curve. Methods:A total of 26 eyes of 26 patients who underwent a SCB procedure for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
(22 reference statements)
0
8
0
1
Order By: Relevance
“… 82 , 83 A possible complication resulting from direct damage to the vortex vein during this procedure is suprachoroidal hemorrhage, which is thought to result from injury to this highly vascular region of the choroid. 84 Furthermore, a recent report has associated a vortex vein varix with recurrent suprachoroidal hemorrhage which occurred in close proximity to the varix. 85 A better understanding of vortex vein anatomy and its variations in healthy and diseased states may curb the unnecessary investigations by retinal surgeons dealing with such eyes.…”
Section: Clinical Significance Of Vortex Vein Imagingmentioning
confidence: 99%
“… 82 , 83 A possible complication resulting from direct damage to the vortex vein during this procedure is suprachoroidal hemorrhage, which is thought to result from injury to this highly vascular region of the choroid. 84 Furthermore, a recent report has associated a vortex vein varix with recurrent suprachoroidal hemorrhage which occurred in close proximity to the varix. 85 A better understanding of vortex vein anatomy and its variations in healthy and diseased states may curb the unnecessary investigations by retinal surgeons dealing with such eyes.…”
Section: Clinical Significance Of Vortex Vein Imagingmentioning
confidence: 99%
“…Mikhail et al 4 reported suprachoroidal hemorrhage because of catheter misplacement in a phakic patient with inferior retinal break. Moreover, Antaki et al 5 studied frequency and type of hemorrhagic complications associated with SCB with respect to the surgical step. The incidence of hemorrhagic complications was 23% (6/26).…”
Section: Discussionmentioning
confidence: 99%
“…8 It is often described as having a steep learning curve. [3][4][5] Undoubtedly, surgeon-related factors, complexity of the surgical technique, and patient selection may significantly affect efficacy, safety, and final outcomes. 9 Individualized approach is recommended for the treatment of primary RRD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations